Design Of A Teaching Kit For Speed And Position Control Of DC Motor - Gunasekaran, Pramila (Universiti Sains Malaysia, 2005)
Direct-current (DC) motors are the first type of motor built and still being used widely. Although, DC motor is more expensive compare to other motors, it is suitable for certain type of control system compare to other motors. The greatest advantage of DC motors is speed control and position control. Basically, these projects are divided into two parts: hardware implementation and software implementation. The hardware implementation is where signal applied will control speed and position by PID controller and the output will be displayed in the digital oscilloscope. This project also requires software implementations to display output signal in the computer panel which involves two microcontroller program. The microcontroller then programmed as an ADC converter and as serial data transmitter, also including Borland C++ Builder to plot a graph of the output signal taken.